Cytokine profile of autologous platelet‐derived eye drops in patients with ocular chronic graft‐versus‐host disease. Issue 2 (18th September 2015) - Valentini, C. G.; Nuzzolo, E. R.; Orlando, N.; Metafuni, E.; Bianchi, M.; Chiusolo, P.; Zini, G.; Teofili, L.
Abstract : Ocular chronic GVHD is efficaciously treated with autologous platelet‐derived eye drops. We investigated the cytokine content of eye drops produced using a non‐gelified lysate obtained from autologous platelet‐rich plasma in six patients with ocular GVHD. In both the responding ( n = 4) and the resistant ( n = 2) patients, the eye drops were significantly enriched with various growth factors, in amounts proportional with the platelet counts. In contrast, chemokine ligand and interleukin levels were similar to those of plasma. The non‐responding patients showed the highest levels of chemokine (C‐X‐C motif) ligand (CXCL)10. These findings provide possible explanations for beneficial or detrimental effects of eye drops.